RENEWABLE ENERGY PRODUCTION FROM PALM BIOMASS BY PYROLYSIS: A PATH TO ACHIEVE ECONOMIC AND ENVIRONMENTAL SUSTAINABILITY - M. Shahidul, Islam (Science International, 2022)
This study aims to unlock the information on the renewable energy production performance from carbon emission potential waste palm biomass. The specific objective of this paper is to reveal the current advancement in the pyrolysis process and its ability to replace fossil fuel with palm biomass. This study also addresses the problem relating to carbon emissions from waste palm biomass for contributing to achieving economic and environmental sustainability in Southeast Asian countries. The research methodology used for this study is reviewing the published research papers. The number of reviewed journals was 75 and published between 2010 to 2022 on research findings relating to the aims of this study. The study revealed that advancements in the pyrolysis process have significantly contributed to producing renewable energy from palm biomass. The temperature range of palm biomass pyrolysis is from 300OC to 9000 C. Energy products of this process are bio-oil, syngas, hydrogen, and bio-char. The energy output of this process is about 17.5MJ per kg of palm biomass. Combined heat and power cycle installed in series with palm biomass pyrolysis for achieving energy production efficiency up to 95%. Palm biomass pyrolysis offers a few benefits. It contributes to substituting fossil fuels with renewable energy and reducing 0.75kg CO2eq emission. The research outcomes listed in this paper would be a guideline for investors, policymakers, researchers, government agencies, and industries for making a strategic plan to implement palm biomass-based renewable energy production plants. The novelty of this study is a presentation of ways to convert waste palm biomass into renewable energy with advanced technology